EXAMINING THE EFFECTS OF GENDER, NATIONALITY AND BIBLIOGRAPHIC INSTRUCTION ON LIBRARY ANXIETY - Abdul Karim, Noor Harun; AnsarI, Novera Afaq (Malaysian Journal of Library and Information Science, 2017)
A 49-item modified version of Sharon L. Bostick’s (1992) Library Anxiety Scale was tested among 367 undergraduate students drawn randomly from a population of 8,432 undergraduate students. The 49-item instrument was administered during classroom hours using a self-reported questionnaire. An 84% response rate was achieved resulting in 308 questionnaires that were returned and were found to be useful. The analysis of data was based on these 308 usable returns. Gender, nationality and bibliographic instruction were employed as independent variables to examine their effects on each of the five (5) library anxiety sub-scales: barriers with service providers, comfort with library services, affective barriers, cognitive barriers and comfort with library technology. The results of running independent sample t-tests on each of the five(5) sub-scales with gender as the independent variable was found to be statistically significant only on the “cognitive barriers “ sub-scale, t (303) = 2.22, p < .05 between male students (M = 7.64, SD = 2.90) and female students (M = 8.42, SD = 2.79). The results of running independent sample t-tests on each of the five (5) library anxiety sub-scales with nationality as the independent variable was found to be statistically significant only on the “affective barriers” sub-scale, t (301) = 2.47, p <.05 between Malaysian students (M = 8.14, SD = 2.22) and non-Malaysians (M = 7.33, SD = 2.17). The results of running independent sample t-tests Mon each of the five (5) library anxiety sub-scales with bibliographic instruction as the independent variable were found to be not statistically significant on all of the five (5) library anxiety sub-scales, p > .05. A 2 X 2 factorial ANOVA was performed to test each of the main effects and interaction effects hypotheses. The results showed that there was a statistically significant interaction effect between gender and bibliographic instruction on the library anxiety sub-scales: (a) affective barriers, F (1, 295) = 5.21, p < .05; (b) comfort with library technology, F (1, 299) = 5.32, p < .05. Statistically significant interaction effects was also found between gender and nationality on the library anxiety sub-scales: (a) barriers with service providers, F (2, 294) = 3.85, p <.05; (b) affective barriers, F (2, 295) = 3.44, p < .05. No statistically significant interaction effects were found between nationality and bibliographic instruction on any of the five (5) library anxiety sub-scales, p > .05. Additionally, no statistically significant main effects were found for each of the independent variables (gender, nationality and bibliographic instruction) on any of the five library anxiety sub-scales, p > .05. Findings suggest that gender acted as a moderating variable for the independent variables nationality and bibliographic instruction. Hence, the variable gender moderates the relationshipbetween the two independent variables (nationality and bibliographic instruction) with the library anxiety sub-scales: affective barriers, barriers with service providers and comfort with library technology. This study represents one of the first to have identified the variable gender as a moderator in explaining the variance in library anxiety among undergraduate library users in a Malaysian university library environment. More studies need to be carried out to identify not only moderators but mediators in the library anxiety phenomenon.